Homing‐pigeon‐based messaging: multiple pigeon‐assisted delivery in delay‐tolerant networks. Issue 8 (5th April 2011) - Guo, Hui; Li, Jiang; Hu, Rose Qingyang; Qian, Yi
ABSTRACT In this paper, we consider the applications of delay‐tolerant networks (DTNs), where the nodes in a network are located in separated areas, and in each separated area, there exists (at least) an anchor node that provides regional network coverage for the nearby nodes. The anchor nodes are responsible for collecting and distributing messages for the nodes in the vicinity. This work proposes to use a set of messengers (named pigeons) that move around the network to deliver messages among multiple anchor nodes. Each source node (anchor node or Internet access point) owns multiple dedicated pigeons, and each pigeon takes a round trip starting from its home (i.e., the source) through the destination anchor nodes and then returns home, disseminating the messages on its way. We named this as a homing‐pigeon‐based messaging (HoPM) scheme. The HoPM scheme is different from the prior schemes in that each messenger is completely dedicated to its home node for providing messaging service. We obtained the average message delay of HoPM scheme in DTN through theoretical analysis with three different pigeon scheduling schemes. The analytical model was validated by simulations. We also studied the effects of several key parameters on the system performance and compared the results with previous solutions. The results allowed us to better understand the impacts of different scheduling schemes on the system performance of HoPM and demonstrated that our proposed scheme outperforms the previous ones. Copyright © 2011 John Wiley & Sons, Ltd.